COMPOUND SENTENCE WITH A RESULTING VERB (International journal of artificial intelligence, 2025)
This article explains general information about compound sentences with a consequent clause, their difference from other compound sentences, the means that connect the consequent clause to the main clause, the views of several scholars on this type of compound sentence, and the types of complex syntactic devices and examples thereof.